Epidemiological characteristics and management of Gram-negative bacteraemia in different immunocompromised hosts: Observational single-center study - Alice Toschi; Renato Pascale; Dino Gibertoni; Riccardo Pasquali; Andrea Grechi; Irene Grassi; Marta Malosso; Ludovica Mangione; Cecilia Bonazzetti; Beatrice Tazza; Matteo Rinaldi; Armando Amicucci; et al. (PLoS ONE, 2025)
Importance Patients with Gram-negative bloodstream infections (GN-BSI) are classified as non-immunocompromised (n-IC) or immunocompromised (IC). However, immunosuppressive condition should not be considered univocally. Objective To investigate epidemiological characteristics, management and outcome of GN-BSI in IC and non-IC patients. Methods Retrospective single-center study of hospitalized patients with GN-BSI conducted over a 7-year period. Patients with GN-BSI were divided in: solid organ transplant (SOT) recipients, patients with hematologic malignancy (HM), patients with metastatic solid cancer (mSC), and non-major IC patients (nm-IC). Results 3544 patients analysed: 76.7% nm-IC, 6.5% SOT, 8.0% HM and 8.8% mSC. SOT and HM patients were younger (SOT: 56.6 ± 13.1 years; HM: 56.4 ± 14.5; nm-IC: 72.4 ± 16.1; mSC: 68.6 ± 13.1, p < 0.001) and had lower CCI value (SOT: 4.5 ± 2.4; HM: 4.1 ± 2.1; nm-IC: 5.5 ± 2.6; mSC: 9.7 ± 2.5, p < 0.001). Urinary tract infection was the most common source of BSI in nm-IC (nm-IC: 50.1%, HM:15%; SOT: 33.3%; mSC: 25.9%, p < 0.001), intra-abdominal infection was the more frequent source among SOT and mSC (SOT:42.3%; mSC: 49.3%, nm-IC: 27.8%, HM:29%; p < 0.001). Primary BSI was the first cause of GN-BSI in HM (HM: 62.1%; SOT: 18.5%; nm-IC: 17.2%; mSC: 10.6%, p < 0.001). The lowest rate of death was observed in SOT and the highest in mSC (SOT 8.2%; nm-IC 13.4%; HM 14.9%; mSC 19.9%, p < 0.001). Relapse rate was highest in SOT (SOT: 18.8%; HM: 11.8%; NMIC: 7.2%; aST: 7.1%, p < 0.001). Follow-up bloodcultures were associated with a lower mortality only among NMIC (HR = 0.317, 95% CI 0.178–0.563, p < 0.001) and aST (HR = 0.198, 95% CI 0.058–0.673, p = 0.010). The role of treatment duration on relapse was not evident in any group, conversely receiving at least 7 days of treatment was associated with a lower risk of 90-day mortality in SOT and HM patients. Conclusions The characteristics and outcome of GN-BSI are peculiar between specific IC categories, therefore a personalized management should be implemented.